2020
DOI: 10.17660/ejhs.2020/85.2.1
|View full text |Cite
|
Sign up to set email alerts
|

SSR fingerprinting of raspberry cultivars traded in Germany clearly showed that certainty about the genotype authenticity is a prerequisite for any horticultural experiment

Abstract: Raspberry (Rubus idaeus L.) cultivars are propagated vegetatively, as many other fruit species from the Rosaceae family. During propagation, mistaken identities of cultivars can be caused by mislabelling plants for various reasons. This poses a problem not only for growers who buy cultivars because of specific characteristics (e.g., resistance) but also for breeders who are being deprived of licensing fees for cultivars under Plant Variety Protection (PVP). In this study, six raspberry cultivars of up to six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Recently, SSRs have been efficiently used for the traceability of cocoa in beans and liquor [ 67 ], evaluations on trueness-to-type of raspberry [ 68 ] and olive [ 69 ] varieties, and to trace monovarietal and polyvarietal wines along the entire production chain [ 36 ]. Microsatellite markers have also been shown to be effective in tracing species characterized by a reduced diversity such as zucchini [ 70 ].…”
Section: Molecular Approaches To Agri-food Analysismentioning
confidence: 99%
“…Recently, SSRs have been efficiently used for the traceability of cocoa in beans and liquor [ 67 ], evaluations on trueness-to-type of raspberry [ 68 ] and olive [ 69 ] varieties, and to trace monovarietal and polyvarietal wines along the entire production chain [ 36 ]. Microsatellite markers have also been shown to be effective in tracing species characterized by a reduced diversity such as zucchini [ 70 ].…”
Section: Molecular Approaches To Agri-food Analysismentioning
confidence: 99%
“…A discrepancy in naming is not the only uncertainty with working with both R. idaeus and R. occidentalis cultivars. Even the genotype authenticity is not to be assumed as certain, as cultivars have been repeatedly found to not be true-to-type, resulting from mix-ups or mutations [41][42][43]. As such, care must be taken with comparisons with other studies, even if they used the same cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of DNA markers have been successfully used for identification of cultivars. Differentiation of cultivated raspberries using random amplified polymorphic DNA (RAPD), amplified fragment length polymorphisms (AFLPs), and simple sequence repeats (SSRs) have been reported by several authors (e.g., Ercisli et al, 2008;Fernández-Fernández et al, 2011;Miyashita et al, 2015;Pinczinger et al, 2020;Simlat et al, 2018;Umar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphic SSR markers appear to be more desired for genotyping vegetatively propagated plants than other DNA fingerprinting methods because they are highly informative (show high polymorphism), reproducible, technically simple (they are simpler than several other techniques), robust, and suitable for automated allele detection and sizing (Nybom and Lācis, 2021;Rafalski and Tingey, 1993). SSR markers for the Rubus species were first developed in early 2000s (Amsellem et al, 2001) and, in subsequent years, a number of studies were conducted involving several plant species (Castillo et al, 2010;Graham et al, 2004Graham et al, , 2002Kalia et al, 2011;Pinczinger et al, 2020). Pinczinger et al (2020) used sixteen SSR markers, divided into six multiplexes, successfully identified the raspberry cultivars, and found that of the 33 samples considered, only 24 samples appeared to be true-to-type, whereas nine samples were found to be wrongly labeled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation